O estado do Rio Grande do Sul frente ao Mercosul - aspectos históricos e econômicos - Silva, Ana Rita Moro da (2006)
Latin-American countries live a new international order featured by the markets globalization and the consequent homogenization of the society which requires from such countries politic-economic reforms and new models of foreign policies aiming the insertion within this new economical context and demanding from them the challenge of getting regionally integrated. Such facts have allowed building the bases of the mercosul. The present study has the objective of analyzing the participation of the state of Rio Grande do Sul on mercosul under the historical and current aspect with the objective of verifying if during the year of 1995 this last one was able to create politic strategies aiming at a positive commercial relationship with the participant countries. In that sense, the first part treats on the historical circumstances of the relationship of the state of Rio Grande do Sul with the platine countries and with Brazil in certain periods. The second one treats on the economical possibilities of the state on mercosul during the year of 1995. Rio Grande do Sul impose itself as region in relation to the platine countries due to the privileged geographic position, for the existence of similar historical experiences and economic interests making possible a real integration and allowing the state to firm its presence in relation to the mercosul. The year of 1995, period of effect of the stage of the integration process, Customs Union, have not provided positive commercial alterations to the state of Rio Grande do Sul due to changes on national economy for the Real Plan and also because the exportations had their bases on the agricultural sector where the countries of the mercosul are more competitive.